(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
This work has as a transversal axis the analysis of the implementation of the Declaration of Alert on Gender Violence against Women in the state of Zacatecas, Mexico, during the period from 2016 to 2019. In this sense, a conceptual framework of violence and its classification, in order to specify gender violence and, its extreme degree, femicides. Likewise, some antecedents of these and the most representative cases that arose in Zacatecas during the study period are briefly addressed, along with the actions of civil society, particularly the Feminist Organization “Olimpia de Gouges” AC, which had a central participation so that the Alert was decreed in the entity in 2018.